Novel packet scheduling algorithm based on cross component carrier in LTE-advanced network with carrier aggregation - Al-Shibly, Mohammed A. M.; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul (2014)
LTE-Advanced provides considerably higher data rates than the early releases of LTE. The carrier aggregation CA) technology allows scalable expansion of effective bandwidth provided to user equipment (UE) through simultaneous utilization of radio resources across multiple carriers. In this paper we propose a new packet scheduling (PS) criterion algorithm that charmingly satisfies the fairness among the different kinds of UEs by designing a weighting factor to proportional fair (PF) packet scheduling (PS) algorithms, while enhancing their throughput performance. The proposed PS algorithm is implemented and validated in a PS module for LTE\LTE-Advanced via system level simulations. Results show that PS-modified algorithms achieve higher throughput for both LTE and LTE-Advanced UEs.